LIKUIDITAS, LEVERAGE, KOMISARIS INDEPENDEN, DAN MANAJEMEN LABA TERHADAP AGRESIVITAS PAJAK PERUSAHAAN - Krisnata Dwi Suyanto; Supramono Supramono (University of Merdeka Malang, 2012)
Tax aggressive was the action designed to reduce taxable income appropriate to tax plan, which could be legalor illegal. This study investigated if extent of liquidity, leverage, independent commissioners and earningmanagement affected corporate tax aggressiveness. Effective tax rate (ETR) and cash effective tax rate (CETR)were used to measure tax aggressiveness. Test was conducted for manufacturing firms which were listed inIndonesian Stock Exchange during the period of 2006-2010. Panel data regression was used to test the hypothesis.The result of the hypothesis was that it failed to find significant relation between liquidity and taxaggressiveness. Independent commissioners had a negative impact to tax aggressiveness, but leverage andearning management had a positive impact to tax aggressiveness.